Improving the methodology of primary school students' mastery activities - Sayfilloyev Azizbek (Genius Journals, 2023)
In Uzbekistan, with the honor of independence, fundamental reforms were implemented in all areas, the Uzbek model of economic development, the national program of personnel training was developed and is being implemented step by step. This article describes in detail the improvement of the methodology of mastering activities of elementary school students.
Keywords: Educational program; pedagogy; methodology; elementary school